Peran Wali Kelas dalam Meningkatkan Kedisiplinan dan Motivasi Belajar Siswa Pondok Pesantren Idrisiyyah Putri - Billa Hadis Wari, Salsa; Wisa Belinda, Ulfi; Ahmad Zulfiqor, Utep (SPT. haria Journal and Education Center Publishing, 2026)
The homeroom teacher has an important role in shaping and changing students' disciplined character, because the homeroom teacher is a source of learning and a role model for students in shaping and changing students' behavior into good individuals, especially in terms of learning discipline. The relationship between the homeroom teacher and students, especially communication relationships, will influence student learning effectiveness because students have confidence that the homeroom teacher will always pay attention to them so that students strive to improve their learning effectiveness. In addition, through reciprocal communication or interaction between the homeroom teacher and students, it influences the upholding of discipline and increases learning motivation. To determine students' discipline and learning motivation and determine the role of the homeroom teacher in improving students' discipline and learning motivation. The method used in this research is a qualitative method by means of observation, interviews and documentation. The role of the homeroom teacher in improving student discipline and learning motivation at the Idrisiyyah Putri Islamic Boarding School, the role of the homeroom teacher as a motivator, class manager, mentor and initiator. two aspects that are interrelated and mutually reinforcing in creating a productive and effective learning environment. Good discipline creates a strong foundation for student learning motivation while learning motivation produces better results in efforts to achieve goals. Therefore, the role of the homeroom teacher in improving student discipline and learning motivation is very important in ensuring that these two aspects are managed well so that students can achieve their maximum learning potential.